C-Spain in the pitch-perfect key of C. - Ochs, Susie
The Gregory Brothers use Macs and Auto-Tuning to make talking heads and politician break into T-painfully infectious song.
Keywords: Logic (Computer file); Macintosh (Computer); Final cut (Electronic resource); Digidesign Digi 002 audio interface